IMPLEMENTASI PENGAMPUNAN PAJAK (TAX AMNESTY), UNDANG-UNDANG PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP BANDAR LAMPUNG - Rasty Yulia; Rina Milyati Yuniastuti; Hesti Widi Astuti (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2020)
The objectives in this study are as follows: The formulation of the problem in this study are as follows: determine the implementation of tax amnesty affecting tax laws in Bandar Lampung KPP, determine the implementation of tax amnesty through tax laws affecting sanctions taxation at the Bandar Lampung KPP, determine taxation laws affect taxation sanctions at Bandar Lampung KPP, determine taxation laws affect individual taxpayer compliance at Bandar Lampung KPP, determine taxation laws through tax sanctions affect individual taxpayer compliance, determining taxation taxation affects the compliance of individual taxpayers, determining implementation (tax amnesty) and tax laws through tax penalties affecting the compliance of individual taxpayers. The methodology in this study is the validity test, reliability test, normality and path analysis. The results of the study are as follows: Structural Equation 1 being as follows: Z = 0.518Y + €, Structural Equation 2 being as follows: Y = -0.034 X1 + 1,947 X2 + € 1, Structural Equation 3 being as follows: Y = 0.143X2 + € 2, Structural Equation 4 being as follows: Z = 0,150Y + € 3, Structural Equation 5 being as follows: Z = 0,986Y + € 4, Structural Equation 6 being as follows: Z = 0,003X1 + 0,986Y + € 5, The structural equation 7 becomes as follows: Z = -0.002X1 + 0.010X2 + 0.982Y + € 6. Keyword - Tax Amnesty, Taxation Law, Tax Sanction, Personal Taxpayer Compliance.